Efficacy of a new Nutraceutical Formulation in preventing acute intestinal inflammation: New therapeutic opportunities for the treatment of diverticulitis? - Silvia D'Alessio; Arianna Vanelli; Stefania Murzilli; Ilaria D'Augello; Silvio Danese (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2022)
Acute diverticulitis is a painful, relatively sudden condition, characterized by the presence of low-grade inflammation in the colonic mucosa. Recent clinical trials supported the use of nutraceutical compounds in the treatment of patients with gastrointestinal disorders, including diverticulitis. To verify the hypothesis that nutraceutical ingredients my prevent diverticulitis development, we tested a combination of different natural active supplements, in a mouse model of acute intestinal inflammation. A nutraceutical formulation was administered daily in a prevention setting, by intrarectal enema. Inflammation severity was monitored using a Disease Activity Index (DAI) score, histological and endoscopic analysis, and quantification of Fecal Calprotectin (FC). Results showed that a combination of cranberry juice, pomegranate extract fruit in ellagic acid and inulin Fibruline®, prevented the development of experimental acute intestinal inflammation. This was confirmed endoscopically, in terms of reduced colon thickness and granularity of mucosal surface. Results were also confirmed histologically, not only by significant reduction of ulcerations, compared to control groups, but also by significant prevention of flogosis and inflammatory infiltration. Nutraceutical ingredients were also able to significantly reduce FC levels, confirming the anti-inflammatory properties of these dietary supplements. Our study supports the potential use of nutraceutical ingredients as a novel therapeutic approach to prevent acute diverticulitis.